Exploring the Mystical Universe! A Comparative Study on Tolerance between Islamic & Christian World - Nazra Zahid Shaikh; Farhana Yasmeen Qadri; Muhammad Safdar Bhatti; Handoko (Andalas International Journal of Socio-Humanities, 2022)
Islam is the religion of peace and harmony as its name suggested by Allah. It is rooted in purity, submission, and obedience. Historically, modern researchers claim Islam is 1400 years old; the youngest religion in the world which was introduced by Prophet Muhammad (PBUH) in 610 A.D. But Muslims believe that this is the oldest and first entered the religion of the world and stepped onto this world with Hadrat Adam (A.S) And Hadrat Hawa (A.S). Contrary to this, Islam has also seen many twists and turns due to its followers and critics. Its original teachings are somehow forgotten by Muslims and misconstrued by other religions. This religion of peace is frequently questioned on ‘peace’ and ‘tolerance’ and is always misunderstood and misinterpreted by the ‘west’, specifically. In recent times, Islam is commonly pigeonholed with ‘extremism’ and ‘terrorism’ and Muslims with ‘terrorists’ and extremists’; without feeling any need to find the truth. Although Islam is the center for spirituality and humanity in real, its general perception is the opposite to it. The purpose of this study is to find out the similarities and differences between the two big religions of the world (as portrayed in scholarly specific poetries) to provide some core similarities in philosophical teachings/understandings. This comparative study has been designed between the works of the two legendary figures of the Islamic & Christian world i.e., Maulana Rumi and Geoffrey Chaucer, respectively. Maulana Rumi is majorly known as a phenomenal Sufi poet/scholar of the 13th century and Chaucer is considered ‘the father of English literature’ and belongs from the 14th century. This qualitative comparison is embedded in the similarities in religion, tolerance, honesty, truth, love, and humanity. It suggests that both poets have used the concept of tolerance as a policy to discover the ‘self’, ‘spirit’, and ‘liberalism’. This study provides evidence based on Islam that peace and tolerance are the soul and blood of this religion. It is also a defense of the evidence that these renowned poets are far more inclusive than most early modern poets of toleration.